Some Observations on the Privy Council - Barwick, The Rt. Hon. Sir Garfield (Journal of Malaysian and Comparative Law, 2019)
Tun Razak Memorial Lecture delivered by the Rt. Hon. Sir Garfield Burwick on 15th August 1985 at the University of Malaya.